Increasing students learning achievement using rewards in the teaching learning english of the fifth grade students of SD Kentungan Depok Sleman Yogyakarta in the academic year of 2004/2005/ Yuli Sapta Wulandari. - YULI SAPTA WULANDHARI (Faculty of Teacher Training and Education Ahmad Dahlan University, 2005)
xvi, 54(110) lbr. : ilus., lamp. ; 30 cm.